2009
DOI: 10.1016/j.febslet.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal degradation of membrane lipids

Abstract: The constitutive degradation of membrane components takes place in the acidic compartments of a cell, the endosomes and lysosomes. Sites of lipid degradation are intralysosomal membranes that are formed in endosomes, where the lipid composition is adjusted for degradation. Cholesterol is sorted out of the inner membranes, their content in bis(monoacylglycero)phosphate increases, and, most likely, sphingomyelin is degraded to ceramide. Together with endosomal and lysosomal lipid‐binding proteins, the Niemann–Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
219
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(227 citation statements)
references
References 214 publications
7
219
0
1
Order By: Relevance
“…Finally, LBPA is a poor substrate for lipases and phospholipases, which has led to the notion that it may be the stereoisomer of other naturally occurring phospholipids (Brotherus et al 1974;Joutti 1979;Thornburg et al 1991;Chevallier et al 2000), as was recently shown (Tan et al 2012). This notion is consistent with observations that LBPA facilitates the degradation of glycosphingolipids in vitro by enhancing the lipid-extraction capacity of saposins (Kolter and Sandhoff 2010). LBPA may also facilitate HSP70 entry into lysosomes and lysosome stabilization (Kirkegaard et al 2010).…”
Section: Restricted Lipid Localization Via Spatially Controlled Synthsupporting
confidence: 77%
“…Finally, LBPA is a poor substrate for lipases and phospholipases, which has led to the notion that it may be the stereoisomer of other naturally occurring phospholipids (Brotherus et al 1974;Joutti 1979;Thornburg et al 1991;Chevallier et al 2000), as was recently shown (Tan et al 2012). This notion is consistent with observations that LBPA facilitates the degradation of glycosphingolipids in vitro by enhancing the lipid-extraction capacity of saposins (Kolter and Sandhoff 2010). LBPA may also facilitate HSP70 entry into lysosomes and lysosome stabilization (Kirkegaard et al 2010).…”
Section: Restricted Lipid Localization Via Spatially Controlled Synthsupporting
confidence: 77%
“…These findings support a mechanism in which SapC inserts directly into the lipid bilayer, thereby disrupting the tightly packed lipids that comprise the target membrane. These SapC-liposome interactions are reminiscent of SapC-membrane interactions observed in the context of glycosphingolipid (GSL) degradation whereby SapC inserts into membrane bilayers to provide lysosomal hydrolases greater accessibility to GSL substrates embedded in model membranes (19)(20)(21)(22). Because membraneassociated SapC facilitates GSL degradation by positioning hydrolytic enzymes, such as β-glucosidase, next to disorganized membrane environments where GSL substrates are accessible (23,24), we tested whether SapC also interacts with CD1 molecules on the surface of model membranes.…”
Section: Resultsmentioning
confidence: 99%
“…FRET efficiency (E) can be determined from the Figure 7 | Current model for regulation of exosomal MVE maturation by a receptor-mediated S1P signalling. During MVE maturation the lipid composition of ILV membrane dramatically changes, that is, the level of ceramide increases at the expense of sphingomyelin, which is rapidly degraded by various sphingomyelinases 65 . Ceramide is sequentially metabolized to S1P by SphK2 via sphingosine.…”
Section: Methodsmentioning
confidence: 99%